TYPES OF CLASSICAL AND MODERN ORGANIC FERTILIZERS - Aripov Bakhtiyor Farmonovich; Akhmedova Zahro Rakhmatovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Humanity's demand for food is growing every year. Like the progress of science and technology, the increase in population does not leave a negative impact on the world around us, nature and its factors. Preserving nature and its wealth, providing high-quality food products to the population poses great challenges for our scientists. this will certainly advance the issues of rational use of plant and animal products and their processing. During our scientific research, we used classical and modern fertilizers to increase plant productivity.